2019
DOI: 10.1111/jcpt.13014
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an innovative surgical pharmacy service to improve patient outcomes—Twelve‐month outcomes of the Enhanced Surgical Medicines Optimization Service

Abstract: What is known and objective: Pharmacists play vital roles in medicines optimization in different care settings. Studies have shown that optimizing patient's pre-existing co-morbidities prior to the surgery leads to better post-operative outcomes. The Enhanced Surgical medicines optimization service (ESMOS) is an innovative surgical pharmacy service introduced at a large teaching hospital in the UK in September 2017 which aimed to reduce the length of stay and post-operative complications in general surgical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…35 The involvement of pharmacists may be promising to improve patient outcomes and speed up patient recovery after surgery. 27,28 In this study, we demonstrated that the CPGT effectively improved PONV for pa- 36 feedback, 36 educational outreach 24,37 and dedicated support. 24 Another strength was the enrolment of a series of patient-related outcomes.…”
Section: F I G U R Ementioning
confidence: 59%
See 1 more Smart Citation
“…35 The involvement of pharmacists may be promising to improve patient outcomes and speed up patient recovery after surgery. 27,28 In this study, we demonstrated that the CPGT effectively improved PONV for pa- 36 feedback, 36 educational outreach 24,37 and dedicated support. 24 Another strength was the enrolment of a series of patient-related outcomes.…”
Section: F I G U R Ementioning
confidence: 59%
“…25 A multidisciplinary clinical pharmacist-led guidance team (CPGT) has gradually been proven as a promising service mode to enhance healthcare quality in previous studies conducted in the First Affiliated Hospital of Zhejiang University (FAHZJ) 19,25,26 and other settings. 27,28 Through active intervention, the CPGT in the FAHZJ has achieved several improvements, such as increasing the rationality of using prophylactic antibiotics in intervention procedures, 26 enhancing the efficacy of cancer pain therapy, and improving postoperative pain of transarterial chemoembolization in patients with hepatocellular carcinoma. 29 In 2015, the enhanced recovery pathway was introduced in the FAHZJ to improve outcomes for surgical patients.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…19 Bansal et al showed a reduction in hospital length of stay compared to the national average in patients undergoing elective major general surgery when pharmacists were involved in perioperative patient care. 20…”
Section: Discussionmentioning
confidence: 99%
“…withholding versus continuing regular medicines), venous‐thromboembolism (VTE) and surgical antimicrobial prophylaxis 9,13,14,16–21 providing guidance on optimising medicines and/or conditions (e.g. smoking cessation, blood glucose levels and diabetes) 9,22–24 supporting stewardship of high‐risk medicines (e.g. opioids, anticoagulants, antimicrobials) 25–30 ensuring quality improvement and cost‐effective care 17,31–34 applying principles of medication safety (e.g.…”
Section: Evidence Of Pharmacist Impact On Surgery and Perioperative M...mentioning
confidence: 99%